A Light' Guide to Energy Savings in Transport - Molloy, Conor (River Publishers, 2023)
This book is a practical guide to finding and delivering energy savings opportunities in transport operations for professional energy managers and energy auditors. Globally, transport is one of the fastest growing energy consumers and emitters of greenhouse gases, predominantly CO₂. The transport sector is also changing quickly (“more change in the last 5 years than in the last 50” – Mary Barra, CEO General Motors). After distance, unladen vehicle weight is the biggest driver of energy consumption in transport, hence this book is called the ‘light’ guide – tongue in cheek. Be warned transport is a huge and complex topic. This practical guide from the convener of EN16247-4:2014, the first European energy audit standard for transport, takes a pragmatic approach to delivering measurable energy and emissions reductions in transport operations. Lessons learnt from the author’s 17 years of experience in persuading operators to deliver measured energy savings in transport are interwoven with tools, tips and shortcuts. That will help energy managers and auditors deliver effective transport energy audits that identify opportunities, prompting action, measured savings and, most importantly, being invited back!